Dialogue Between the State and Society in Uzbekistan: Political and Communication Analysis - Babaev Tolibjon Abdujalilovich (Periodica Journal, 2023)
This scientific article analyzes the formation and development of a system of dialogue with the people in Uzbekistan based on the theory of political communication. The democratic reforms carried out in recent years and the "feedback" mechanism, which is considered an important element of civil society, are identified. Based on the study of various theoretical sources and legal documents, scientifically substantiated conclusions are made.
Keywords: Uzbekistan; dialogue with the people; appeals